PECULIARITIES OF USING INTERACTIVE TECHNOLOGIES IN THE MORPHOLOGY LEARNING PROCESS - Tsofal Л.С. (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the interactive studying, peculiarities of using the interactive technologies on the lessons of the Ukrainian language. The author shows the specific character of their introduction into the process of studying the morphology.